2022
DOI: 10.1111/gtc.12983
|View full text |Cite
|
Sign up to set email alerts
|

Local anesthetic lidocaine induces growth suppression of HeLa cells by decreasing and changing the cellular localization of the proliferation marker Ki‐67

Abstract: Although surgery is a basic therapy for cancer, it causes inflammation and immunosuppression, often resulting in recurrence and metastasis. Previous studies have suggested that anesthetic management influences the prognosis of cancer surgery patients. Administration of local anesthetics, such as lidocaine, for pain control reportedly improves their clinical outcomes; however, the precise underlying mechanism has not been fully elucidated. The growth of human embryonic kidney (HEK) 293T and cervical cancer HeLa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…From this cell cycle analysis, levobupivacaine and chloroprocaine slightly activated cell cycle arrest at the S phase, while ropivacaine remarkably induced cell cycle arrest at the G2/M phase [90]. Interestingly, lidocaine, a VGSC inhibitor that was reported to decrease cell proliferation and reduce cancer cells' migration and invasion [64,91,92], showed a mild effect on cell cycle arrest at the S phase, with no significant influence on the migration of MDA-MB-231 cells at its antiarrhythmic plasma concentration (10 µM) after 24 h of treatment [90]. Additionally, the treatment of lidocaine at 100 µM was reported to inhibit cell growth at 72 h and increase apoptosis at 48 h; however, it did not show a significant effect on cell cycle arrest in hepatocellular carcinoma HuH7 and HepaRG cells (both cell lines had no report of VGSCs' expression) [93].…”
Section: Cell Cycle Analysis In Response To Sv188 Treatmentmentioning
confidence: 90%
See 2 more Smart Citations
“…From this cell cycle analysis, levobupivacaine and chloroprocaine slightly activated cell cycle arrest at the S phase, while ropivacaine remarkably induced cell cycle arrest at the G2/M phase [90]. Interestingly, lidocaine, a VGSC inhibitor that was reported to decrease cell proliferation and reduce cancer cells' migration and invasion [64,91,92], showed a mild effect on cell cycle arrest at the S phase, with no significant influence on the migration of MDA-MB-231 cells at its antiarrhythmic plasma concentration (10 µM) after 24 h of treatment [90]. Additionally, the treatment of lidocaine at 100 µM was reported to inhibit cell growth at 72 h and increase apoptosis at 48 h; however, it did not show a significant effect on cell cycle arrest in hepatocellular carcinoma HuH7 and HepaRG cells (both cell lines had no report of VGSCs' expression) [93].…”
Section: Cell Cycle Analysis In Response To Sv188 Treatmentmentioning
confidence: 90%
“…Additionally, the treatment of lidocaine at 100 µM was reported to inhibit cell growth at 72 h and increase apoptosis at 48 h; however, it did not show a significant effect on cell cycle arrest in hepatocellular carcinoma HuH7 and HepaRG cells (both cell lines had no report of VGSCs' expression) [93]. A recent study on the treatment of lidocaine in cervical cancer HeLa cells that expressed Na V 1.6 [65] found that this drug significantly inhibited the cell growth at 0.3 mM by reducing a proliferating protein, Ki-67 (MKI67), and a cell cycle analysis indicated that lidocaine significantly induced arrest at the G0/G1 phase and decreased cells' population at the G/M and S phases in a dose-dependent manner [91]. In addition, the knockdown of Na V 1.5 in oral squamous cell carcinoma (OSCC) HSC-3 cells caused cell cycle arrest at the G1 phase and a drastic reduction in cell migration and invasion [94].…”
Section: Cell Cycle Analysis In Response To Sv188 Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…LAs also exhibit short-term cytostatic and long-term cytotoxic properties. 27 Interestingly, the chemical structure (ester or amide) does not seem to dictate cytotoxicity activity, whereas it is worth noting that chloroprocaine and prilocaine, which possess a short duration of action, induce fewer effects on cancer cells than agents with an extended time of efficacy. 28 Among the tested LAs, bupivacaine appears to be the most cytotoxic, while procaine is the least.…”
Section: Preclinical Investigationmentioning
confidence: 99%